Premature germination of resting spores as a means of protecting brassica crops from Plasmodiphora brassicae Wor., (clubroot). (November 2015) - Mattey, Michael; Dixon, Geoffrey R.
Abstract: Clubroot disease causes substantial yield and quality losses in broadacre oil seed and intensive vegetable brassica crops worldwide. The causal microbe Plasmodiophora brassicae Wor., perennates as soil-borne dormant resting spores. Their germination is triggered by exudates from host roots. A valuable addition to sustainable integrated control strategies could be developed by identifying and synthesising the molecules responsible for stimulating resting spore germination. This paper reports experiments in which stimulatory exudates were collected from brassica roots following exposure to infective stages of P. brassicae . Analyses identified a germination signalling molecule of circa 1 kDa formed of glucose sub-units. Mass spectral analyses showed this to be a complex hexasaccharide carbohydrate with structural similarities to the components of plant cell walls. This is the first report of a host generated hexasaccharide which is capable of stimulating the germination of resting spores of P. brassicae . The implications for environmentally benign control of clubroot are discussed briefly. Highlights: Hexasaccharide triggers resting spore germination in Plasmodiphora brassicae . New form of biological control which is environmentally friendly. Previously unreported messaging chemical in soil borne microbes.